Un sistema automatico per la misura di tre componenti del campo geomagnetico utilizzante un magnetometro a precessione nucleare - P. PALANGIO; A. MELONI; A. DE SANTIS; Q. TACCETTI (Annals of Geophysics, 1981)
Recording in digital form from the start is almost a necessary step in Geomagnetic Observatories; we propose in this paper a simple method based on the use of a proton precession magnetometer equipped with two Helmholtz coils. A small microprocessor has been used to transform the signal frequency measured by the electronic counter to obtain the components absolute values and to automatize the set of measures. A sophisticated equipment for the current generation and control was necessary to maintain the current flowing in the Helmoholtz coils within 2 [iA for successive measurements. To maximize the signal coming from the sensor inside the coils, for the different components, a simple arrangement of two ortogonal small coils in only one sensor has been made. The system proposed can furnish a very good stability and accuracy (~ 1.5 riT) in the measured components (H, D, Z) and could avoid the absolute measurements. The time sampling for the complete set of components is ~ 20 sec; the instrument can be used then to obtain informations of the geomagnetic variations with period T > 1 min. The Observatory use is suggested for an automatic hourly means computation.